Decision-Making Process of Internal Whistleblowing Behavior in China: Empirical Evidence and Implications - Zhang, Julia (Journal of business ethics, 2009)
In response to the lack of empirical studies examining the internal disclosure behavior in the Chinese context, this study tested a whistleblowing-decision-making process among employees in the Chinese banking industry. For would-be whistleblowers, positive affect and organizational ethical culture were hypothesized to enhance the expected efficacy of their whistleblowing intention, by providing collective norms concerning legitimate, management-sanctioned behavior. Questionnaire surveys were collected from 364 employees in 10 banks in the Hangzhou City, China. By and large, the findings supported the hypotheses. Issues of whistleblowing in the Chinese context and implications were discussed.